Financial Inclusion and Well-Being of Marginalized Street Vendors in Chitwan - Chhetri, Guna Raj; Poudel, Pawan (Madhyabindu Journal, 2025)
This study aims to examine the determinants of financial inclusion and investigate its influence on the financial well-being of marginalized street vendors in Chitwan, utilizing social capital theory as a theoretical framework. The research is based on quantitative analysis, with data collected from 205 respondents using structured questionnaires distributed through offline and online channels. Convenience sampling was employed to gather data. The study used descriptive and inferential statistical methods and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). Among the five dimensions of financial inclusion determinants, financial literacy, availability, usage, and affordability significantly influenced financial inclusion, whereas accessibility did not have a significant impact. The findings further revealed that financial inclusion significantly impacts the financial well-being of marginalized street vendors in Chitwan. The study is limited to marginalized street vendors in Chitwan and may not be generalizable to other contexts or populations. Future research should explore the interrelationships between individual financial inclusion and financial well-being in broader or comparative settings for a comprehensive understanding of this relationship. The study provides valuable insights for policymakers, financial institutions, and development organizations aiming to enhance financial inclusion and promote financial well-being among marginalized communities. It highlights the need for targeted interventions in financial literacy, service availability, usage, and affordability.